Microplastics in glaciers of the Tibetan Plateau: Evidence for the long-range transport of microplastics - Zhang, Yulan; Gao, Tanguang; Kang, Shichang; Allen, Steve; Luo, Xi; Allen, Deonie (The Science of the total environment, 2021)
Microplastics are globally prevalent on a large scale in various marine and terrestrial environments, including Arctic snow and precipitation in protected areas of the United Sates. However, reports of microplastics from glaciers are rare, especially for the Tibetan Plateau (TP), which is widely known as the world's Third Pole and Asian Water Tower. Adjacent to human settlements in South Asia, East China, and Central Asia, the TP features regular cross-border air pollution (e.g., black carbon and mercury), which can affect its vulnerable and pristine environments. In previous studies, abundant microplastics have been reported from Tibetan rivers/lakes water and sediments, and surface soils. We detected microplastics in glacier surface snow on the TP, which were isolated from the impact of human activities, indicating that microplastics can be transported over long distances. This evidence is expected to be significant for understanding the atmospheric transport of microplastics to the TP, and provides a global perspective on the microplastic cycle. [Display omitted] •Tibetan Plateau pristine environment has been affected by atmospheric pollutants through long range transport.•Microplastics have been detected from glacier surface snow in Tibetan Plateau.•Atmospheric transport played an important role on microplastics into the plateau.•Ice core may provide an opportunity to study history variations of microplastics.